Application of GIS Technology for Determining Sea Fish Capital Potential on Mobile Apps - Sahulata, Reynoldus Andrias; Brillian, Putri; Lahengke, Gabriela; Yudha, Yoshua Shandy (CogITo Smart Journal, 2024)
The ocean is the central source of livelihood for fishermen. Fishermen depend heavily on their sea catch. Fishermen often need more certainty because, as is often the case, the spot where they go for fishing is not necessarily the site of the fish. Remote sensing technology, such as the Aqua MODIS satellite, provides two vital advantages: the exact location of the fish and, importantly, guidance to the exact spot of the fish. This guidance can be a reassuring tool for fishermen. Using GIS technology on smartphones, fishermen can ensure the fish's position. The distribution of sea surface temperature and chlorophyll-a is analyzed to determine the coordinates. The purpose of this research is to use the React Native platform to create a mobile application that uses Geographic Information System (GIS) and Global Positioning System (GPS) technologies and is accessible through smartphones. This research adopts a prototyping model method consisting of several stages: Information Gathering, Quick Planning, Quick Design, Software Development, Testing and Deployment, and Results. The application developed can run smoothly from the log-in stage to predictive visualization of fish positions in the ocean. However, further research needs to be done to improve some features.